The influence of the Zionist movement in the British legislative and operational authorities (1897-1948) (Journal of the College of Basic Education, 2022)
Many British politicians affected the principles of Zionist movement, were an integral part of British policy. Britain held the Six-Pico Treaty in 1916 with France in preparation for Palestine control, the British government issued in 1917. Britain has worked for a national homeland in Palestine and opened its doors for Jewish migration. The United Nations resolution I acknowledged to divide Palestine and the Jewish army was committed against the Arabs and declared Israel in 1948.